Two essays on corporate finance : essay 1 (CEO turnover and earnings quality), essay 2 (cross-country IPOs : what explains differences in underpricing?) - Dai, Lili (2011)
This paper investigates the relation between CEO turnover and earnings quality. We find that CEO turnover is more likely when earnings quality is poor. After we decompose earnings quality into innate earnings quality and discretionary earnings quality, we find that CEO turnover is significantly associated with the latter but not the former. The findings are economically significant. Specifically, an increase in the inverse measure of earnings quality from the 10th percentile to the 90th percentile increases the predicted probability of CEO turnover by 26 percent. The results concentrate on forced turnovers and are not explained by earnings restatements, failure to meet analysts’ forecasts, or risks. Further investigations suggest that the relation between earnings quality and CEO turnover is stronger for firms with less entrenched CEOs and better corporate governance. Among CEOs who are forced out, we find that career prospects are dimmer for those whose prior tenure is associated with poor discretionary earnings quality. We study the impacts of country-level information asymmetry, investors' home-country bias, effectiveness of contract enforcement mechanisms, and accessibility of legal recourse on IPO underpricing in 36 countries around the globe.